The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mabi.201700353
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N‐methylvinylamine)‐Based Copolymers for Improved Gene Transfection

Abstract: Poly(N-methylvinylamines) with secondary amines can form complexes with plasmid DNA (pDNA) and provide transfection efficiency in HeLa cells in the same order as linear polyethyleneimine but with higher cell viability. Chemical modifications of poly(N-methylvinylamine) backbones are performed to further improve transfection efficiency while maintaining low degree of cytotoxicity. In a first type of polymer, primary amino groups are incorporated via a copolymerization strategy. In a second one, primary amino an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The polymers did not present any cytotoxicity after removal of the cobalt complex. For example, PVAc/C 60 nanohybrids were hydrolyzed into water-soluble PVOH/C 60 and exploited in photodynamic cancer therapy applications. , Also, well-defined cobalt-free poly­(vinyl amine)­s resulting from hydrolysis of poly­(vinyl amides) formed by CMRP demonstrated excellent cell viability and high potential for gene transfection. , …”
Section: Organocobalt(iii) Complexes Bearing Bis(acetylacetonate)-typ...mentioning
confidence: 99%
“…The polymers did not present any cytotoxicity after removal of the cobalt complex. For example, PVAc/C 60 nanohybrids were hydrolyzed into water-soluble PVOH/C 60 and exploited in photodynamic cancer therapy applications. , Also, well-defined cobalt-free poly­(vinyl amine)­s resulting from hydrolysis of poly­(vinyl amides) formed by CMRP demonstrated excellent cell viability and high potential for gene transfection. , …”
Section: Organocobalt(iii) Complexes Bearing Bis(acetylacetonate)-typ...mentioning
confidence: 99%
“…Free radical polymerization has been utilized to yield different PVam structures, which increased transfection efficiencies slightly above PEI comparisons 29 . The same group utilized a secondary amine derivative of PVam for improved transfection efficiency and low toxicity 30 . However, Tian et al is the first study to carefully optimize unmodified PVam, and compare it with PEI in an in vivo context 27 .…”
Section: Recent Progress and Developmentmentioning
confidence: 99%
“…To improve the transfection efficiency of the amine-modified PVA polymers, some approaches were taken, such as the simultaneous administration of chloroquine (Oster et al, 2004), grafting of poly(lactic-co-glycolic acid) (PLGA) chains onto the DEAPA-PVA backbone [DEAPA-PVA-g-PLGA polymer consisting of a PVA (MW 15,000 g/mol) grafted onto PLGA with activation by DEAPA as an amine function] (Nguyen et al, 2008;Oster et al, 2006), or by increasing the (Dréan et al, 2018) amine density (Unger et al, 2007). In the study by Unger and co-workers (Unger et al, 2007), the authors showed that the degradation of DEAPA-PVA-g-PLGA copolymers depended on the degree and type of amine substitution and varied from <5 days to more than 4 weeks.…”
Section: Pvamentioning
confidence: 99%